Personal and Scientific Characteristics of Positive and Negative Role Models among Medical Educators from the Viewpoint of Dentistry and Pharmacy Students in Kerman University of Medical Sciences Iran - Maryam Esmaeili; Ali Akbar Haghdoost; Ali Akbar Haghdoost; Amin Beigzadeh; Bahareh Bahmanbijari; Azam Bazrafshan (Kerman University of Medical Sciences, 2013)
Background & Objective: Several factors play an integral role in the quality of higher education and improving its processes Professional role modeling is one of the most determining factors in achieving educational goals and fostering better learning Hence the aim of this study was to investigate the scientific characteristics of positive and negative role models among medical educators from the viewpoint of the dentistry and pharmacy students in Kerman University of Medical Sciences (Kerman Iran) Methods: In this descriptive analytical crosssectional study a structured and selfadministered questionnaire was completed by 94 senior pharmacy and dentistry students The questionnaire contained prespecified items in 3 sections relating to the demographic characteristics of respondents and scientific characteristics of positive and negative role models Results: The highest mean scores for positive role models were given to features as being respectful to colleagues (875) being knowledgeable (852) having teaching competencies (849) being good tempered (845) and being kind (843) There was not a statistically significant difference between the positive role models [age gender education level (basicclinical)] and the scientific rank The highest mean scores for negative role models were given to the features as deserving blame (697) having no teaching competencies (641) not being kind (609) not being a good manager (608) and not being respectful to students (603) There was only a significant difference between the negative role models and scientific rank (P = 0029) Totally 2 positive and 3 negative characteristics were identified for professional and nonprofessional role models These characteristics can be classified into ethical behavior and communication educational and managerial skills and scientific competencies There was not a statistically significant difference regarding the association between the scientific characteristics of positive and negative role models and the general characteristics of the respondents in terms of age variable Conclusion: Our results suggested that the positive and negative characteristics of teachers formed a significant part in their acceptance and choosing them as role models from the perspectives of students To achieve the educational goals and improving our higher education system special attention should be given to these aspects as personality professionalism and scientific characteristics